Implementation of Zoning System in Acceptance of New Students at SMAN 12 in Pekanbaru City - Neni Triana (International Journal of Integrative Sciences, 2023)
One of the objectives of the zoning system regulation is the equalization of education for all students. In the effort to implement this zoning system, there are still many obstacles felt by the school, such as the limited number of school quotas in accepting students. From the parents and students there are problems with this zoning system because students cannot enter the desired school and limited quotas or the distance of the house and as if outside the zoning boundaries, causing confusion in sending children to school because they do not enter the school zoning that students want. The purpose of this research is how the implementation of the zoning system in the acceptance of students at SMAN 12 in Pekanbaru City. The research is qualitative research. Descriptive method with research informants consisting of Principal, students and parents of students. Data collection techniques used are interviews and documentation studies. The type of data and data sources used primary data and secondary data